2017
DOI: 10.1111/ocr.12177
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency, effectiveness and treatment stability of clear aligners: A systematic review and meta‐analysis

Abstract: Despite claims about the effectiveness of clear aligners, evidence is generally lacking. Shortened treatment duration and chair time in mild-to-moderate cases appear to be the only significant effectiveness of clear aligners over conventional systems that are supported by the current evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
116
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 18 publications
7
116
0
5
Order By: Relevance
“…Systematic reviews have evaluated the efficiency of orthodontic treatment with clear aligners and they suggested that the outcomes are not as accurate as those with fixed appliances [14][15][16]. On the other hand, treatment done with clear aligners present some advantages such as overall decreased treatment and chair time in patients with mild to moderate malocclusions [17]. Besides that, studies have shown that gingival health tends to be better, based on the periodontal health index, in patients treated with clear aligners [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have evaluated the efficiency of orthodontic treatment with clear aligners and they suggested that the outcomes are not as accurate as those with fixed appliances [14][15][16]. On the other hand, treatment done with clear aligners present some advantages such as overall decreased treatment and chair time in patients with mild to moderate malocclusions [17]. Besides that, studies have shown that gingival health tends to be better, based on the periodontal health index, in patients treated with clear aligners [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of tooth movement is important to set up the final treatment goals, to calculate treatment times and costs based on the available evidence. There are five previous systematic reviews (SR) that discussed the effectiveness of clear aligners . The first SR, published 14 years ago, only included two studies with high risk of bias (RoB) so it could not conclude anything about predictability of tooth movement with clear aligners.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the included studies (63%) had a high RoB. Another SR published the same year included only four studies for qualitative analysis pointing towards insufficient evidence with regard to the effectiveness of clear aligner therapy as compared to fixed appliance therapy. Two recently published SRs included articles up to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The CAT is increasing in popularity given its advantages over conventional fixed appliances in terms of esthetics, oral hygiene, comfort for patients, shortened treatment duration, and chair time in mild to moderate cases, despite the higher costs and the unpredictable outcome in certain cases. [3][4][5][6] Numerous studies have investigated the accuracy and efficiency of this technology. Kravitz et al 7 studied 37 nonextraction patients and found that the mean accuracy of tooth movement with Invisalign was only 41%.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have researched treatment outcomes, 3,5,10,11 the biomechanical mechanisms by which CAT exerts its effects remain unknown, and it is challenging to assess the force imparted by these clear aligners. Finite element analysis has been used to provide quantitative and detailed data simulating the physiological tissue reactions during treatment, 12 but finite element analysis results depend directly on the input data, the accuracy of the model, and the boundary conditions and solution, while the accepted physical property values of the supporting tissues still include many discrepancies.…”
Section: Introductionmentioning
confidence: 99%